ELECTRODE MODIFICATION FOR CO2 ELECTROCHEMICAL REDUCTION BY ELECTRODEPOSITION METHOD - Alfath Chaniago, Muhammad
Indonesia is one of the countries with a fairly high use of fossil energy. The use of fossil energy which is quite high has an impact in the form of greenhouse gas emissions that are not friendly to the environment. Therefore, greenhouse gas emissions, especially CO2, need to be reduced so that the phenomenon of global warming can be minimized. There are several technologies in an effort to reduce CO2 gas, one of which is electrochemical reduction technology. Electrochemical reduction technology can be developed to convert CO2 into other compounds. In this study, another compound produced from CO2 conversion is formic acid. Formic acid can be applied in various types of industries, one of which is the food industry. Electrochemical reduction of CO2 gas uses Pb-Sn alloy as cathode and Pt-Ir alloy as anode. The catholyte used was 0.5 M KHCO3 and the anolyte used was 0.1 M H2SO4. The main focus of this research is the electrode used, namely Pb-Sn which will be modified with Pb using the electrodeposition method. The electrolyte used had a composition of 0.01 M Pb(NO3)2, 0.1 M HNO3 and 0.01 M NaF. Variations carried out in this experiment are variations in current density and electrodeposition time. After that, current efficiency as the results of electroreduction experiments using modified and unmodified electrodes compared. The increase in the electrodeposition current density gives a surface pore structure with a smaller diameter. The increase in electrodeposition time results in a more even structure of the cathode surface. Modification of the electrode with Pb electrodeposition gives a higher current efficiency for all variations of electrodeposition compared to the electrode without modification. The best current efficiency was obtained from the modified electrode with variations in electrodeposition current density of 3A/cm2 and electrodeposition time of 5 seconds, which was 23%. This value increased by 18% compared to the electrode without modification.